What Works? Identifying and scaling up successful innovations in Canadian energy regulatory decision making - Larkin, Patricia (Université d'Ottawa | University of Ottawa, 2021)
In a new research study, undertaken in collaboration with CAMPUT (Canada’s Energy and Utility Regulators), Positive Energy Senior Research Associate Dr. Patricia Larkin analyzes the benefits, barriers, trade-offs, and success factors for regulatory innovation in two vital areas: relationships between policymakers and regulators, and regulators’ public engagement processes. Drawing on the research findings, she proposes a suite of questions that regulators might ask themselves as they embark on innovations within their organizations and beyond.
Keywords: Public Confidence; Energy Policy; Energy Regulation; Regulatory innovation; Canada; Positive Energy; Public Utilities